Peran Palang Merah Indonesia Dalam Penanggulangan Bencana Alam - Imelda I; Nafisah Nadia; Ummu Nabila Marpaung; Usiono U (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the role of the Indonesian Red Cross (PMI) in disaster management. The research used is a qualitative descriptive study, employing literature review as the method. Data sources were gathered from previous studies such as journals, scientific articles, books, and other relevant materials that support the topic. The results of this research indicate that the role of PMI volunteers in non-disaster situations can be divided into two phases: mitigation and potential disaster response. In the  mitigation  phase,  volunteers  are  involved  in  training,  outreach,  information dissemination, raising awareness, and conducting disaster simulations. When there is a potential  disaster,  they  monitor  threats, provide  emergency  response  training,  and prepare basic needs and recovery equipment. During an actual disaster, volunteers conduct search  and  rescue,  evacuation, provide field kitchens,  temporary  shelters, protection for  vulnerable  groups,  and  assist  in  emergency  recovery,  information dissemination, and psychosocial support for victims.